Pulmonary endarterectomy for chronic thrombo-embolic pulmonary hypertension: an institutional experience - (:unkn) unknown (OXFORD UNIV PRESS INC, 2013)
Pulmonary endarterectomy (PEA) is the treatment of choice for patients with chronic thrombo-embolic pulmonary hypertension (CTEPH). The aim of this study was to review our initial experience since the implementation of our program. Data were collected prospectively on all patients who underwent PEA between March 2011 and March 2012. Forty-nine patients (20 male, 29 female, mean age 47.7 years) underwent surgery. The preoperative New York Heart Association class distribution showed the majority to be in class III or IV (n = 40). Mortality rate was 14.2% (n = 7) and the morbidity rate was 26.5% (n = 13). After PEA, the durations of mechanical ventilation, intensive care stay and hospital stay before discharge were 49.7 +/- 46.1 h, 6.5 +/- 5.0 days and 12.9 +/- 7.5 days, respectively. The systolic and mean pulmonary artery pressure (PAP) fell significantly from 87.0 +/- 26.6 mmHg and 53.8 +/- 14.5 before, to 41.5 +/- 12.4 mmHg and 28.5 +/- 10.5 after surgery (P < 0.001 and P < 0.001, respectively). Pulmonary vascular resistance (PVR) also improved significantly from 808 +/- 352.0 to 308 +/- 91 dyn center dot s center dot cm(-5) (P < 0.001). Univariate analysis showed that preoperative systolic PAP, tricuspid annular plane systolic excursion, right atrial volume, right atrial pressure, forced expiratory volume in 1 s, forced vital capacity, preoperative PVR, postoperative PVR, the duration of circulatory arrest and postoperative use of extracorporeal membrane oxygenation were risk factors for mortality (P < 0.05). According to multivariate analyses, only prolonged mechanical ventilation was selected as predictive risk factor for morbidity (P = 0.005). After a median follow-up of 6.1 months, two patients died due to cerebrovascular disease and one patient needed targeted pulmonary hypertension therapy. The rest of the 39 patients showed marked improvements in their clinical status. Starting a pulmonary endarterectomy program with acceptable mortality and morbidity rates and satisfactory early-term outcomes increases awareness of the CTEPH and surgery. Preoperative factors can primarily predict postoperative outcome after PEA. Identifying the risk factors in order to achieve a good result is important for the success of a PEA program. Therefore all patients diagnosed with CTEPH should be referred for consideration of PEA in a specialized centre.
Keywords: Chronic thrombo-embolic pulmonary hypertension; Pulmonary endarterectomy; Mortality; Outcome; SINGLE-CENTER EXPERIENCE; TRICUSPID REGURGITATION; CIRCULATORY ARREST; THROMBOENDARTERECTOMY; SURGERY; SUPPORT